Eine vormasoretische Textaneignung in der Hoseaschrift? - Schütte, Wolfgang (Biblische Notizen, 2009)
In all addresses of Hosea there are only four (Hos 2,8.18; 9,10; 10,9) of MT not testified by LXX, but one (Hos 2,20) of LXX not testified by MT. Because of their special intentions these differences of tradition can be understood as an adaption of the written text of Hosea to the historical situation of jewish people in Palestine (MT) and abroad (LXX) in the last centuries BCE.